2000
DOI: 10.1211/0022357001777621
|View full text |Cite
|
Sign up to set email alerts
|

Balicalin, the Predominant Flavone Glucuronide of Scutellariae Radix, is Absorbed from the Rat Gastrointestinal Tract as the Aglycone and Restored to its Original Form

Abstract: When baicalin was orally administered to conventional rats, it was detected in their plasma for 24 h after administration, but baicalein, the aglycone of baicalin, was not detected. However, when baicalin was given to germ-free rats, only a small amount of baicalin was detected in their plasma within 2 h after the administration, its AUC0-lim (the area under the concentration-time curve from 0 to last determination time) being 12.0% of that in conventional rats. Subsequently, a considerable amount (55.1 +/- 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
175
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(189 citation statements)
references
References 9 publications
12
175
2
Order By: Relevance
“…16 On the basis of the results of reported studies, 6,16 it is suggested that the enterohepatic recycling of BA played an important role in the absorption of BA through the gastrointestinal tract: Thus, BA itself was poorly absorbed from the rat gastrointestinal tract, where it was hydrolyzed to its aglycone moiety, namely baicalein, by intestinal bacteria; then the baicalein was absorbed rapidly and converted back to BA in the systemic circulation, resulting in the second absorption peak. 40 The plasma drug concentration-time data of BA was analyzed with a noncompartmental model, and the results of pharmacokinetic parameters are shown in Table 3. Significant differences in the pharmacokinetic parameters of BA were observed between BA-CMC and BA-LP.…”
mentioning
confidence: 99%
“…16 On the basis of the results of reported studies, 6,16 it is suggested that the enterohepatic recycling of BA played an important role in the absorption of BA through the gastrointestinal tract: Thus, BA itself was poorly absorbed from the rat gastrointestinal tract, where it was hydrolyzed to its aglycone moiety, namely baicalein, by intestinal bacteria; then the baicalein was absorbed rapidly and converted back to BA in the systemic circulation, resulting in the second absorption peak. 40 The plasma drug concentration-time data of BA was analyzed with a noncompartmental model, and the results of pharmacokinetic parameters are shown in Table 3. Significant differences in the pharmacokinetic parameters of BA were observed between BA-CMC and BA-LP.…”
mentioning
confidence: 99%
“…Scutellariae flavonoids are reported to be extensively metabolized after being absorbed mainly in the form of aglycones from the gastrointestinal tract. 16 Accordingly, aglycones such as baicalein and wogonin are likely to exist in plasma at a lower concentration than glycones, possibly less than 0.1 μg/mL. This was mentioned as a possible reason why the aglycones could not be detected by the authors of the previous study.…”
Section: Introductionmentioning
confidence: 89%
“…Baicalein-6-O-β-glucopyranuronoside has been detected as a major metabolite besides baicalin in plasma after oral administration of baicalin to rats (13). The conjugated metabolites are readily hydrolyzed by the enzyme β-glucuronidase/sulfatase to free aglycone, and baicalin has been found to be absorbed from the gastrointestinal tract as its aglycone, which is restored to the baicalin parent drug by glucuronidation in the intestine and the liver in vivo (14). The present study investigated metabolites of baicalin in rabbit plasma.…”
Section: T He Root Of Scutellaria Baicalensis Georgi (Huangqin In Chimentioning
confidence: 99%